Regional context in plant breeding priorities: The case of groundnuts in West and Southern Africa - Mbugua Gitonga, Agnes; Rutsaert, Pieter; Khaemba, Colleta; Kitoto, Victor; Muindi, Pauline; Bunter, Dan (CGIAR Science Program on Breeding for Tomorrow, 2025)
The regional context significantly influences plant breeding priorities, particularly for crops such as groundnut with diverse uses across regions. This study investigates how local factors in West Africa (Nigeria) and Southern Africa (Malawi) shape breeding decisions by analyzing household consumption patterns, market demand, and value chain roles. Using qualitative data from focus group discussions and key informant interviews, the research reveals that end-use preferences such as oil content, haulm quality, and grain characteristics vary significantly between regions and stakeholders. For example, Nigerian markets emphasize oil content and haulm yield, whereas Malawian markets prioritize grain color, grain size, and aflatoxin tolerance for exports. The findings underscore the necessity of incorporating localized market intelligence into Target Product Profiles to improve breeding efficiency, variety adoption, and overall impact. A demand-led breeding approach that acknowledges nuanced regional contexts is essential for aligning breeding outcomes with user needs and maximizing returns on investment.